Development of Foam Adhesive Remover for Aircraft Applications - DING Meng, ZHU Hao, TAN Xuecai, CAI Peng, YANG Zongbang (Cailiao Baohu)
In the deep repair process of aircraft wing endplates， spoiler and other parts， the efficient removal of foam adhesive without damaging the aluminum alloy has been paid much attention in the field of aviation repair.In this study，the cured products of foam adhesive were analyzed using infrared spectroscopy and thermogravimetric analysis.Based on the swelling theory， dichloromethane was identified as the primary solvent for the adhesive remover.TiO2-modified SiO2 nanocapsules were introduced into dichloromethane as adsorbents and slow-release agents to reduce VOC emissions， extend the operating time of the adhesive remover， and improve its performance through mechanisms such as physical adsorption， physical isolation and slow release.Meanwhile， paraffin and polyethylene sheets were used as surface barriers， and Halox630 corrosion inhibitor was added to the formulation of the adhesive remover to effectively reduce the volatilization of the remover and the corrosion of the substrate.Results showed that the developed foam adhesive remover exhibited excellent degumming performance on residual foam adhesive on the surface of aluminum alloy， as well as outstanding softening and swelling effects on thermosetting adhesives.